A Sociolinguistic Study of Lifestyle and Language Change among Young Adults - Firda Sarah Latifah (Jurnal Dieksis ID, 2026)
This study explores the relationship between lifestyle patterns and language change among young adults using a sociolinguistic approach. Language change is viewed as a socially driven process influenced by everyday interaction, media exposure, and engagement with contemporary trends. The objectives of the study include describing the lifestyle characteristics of young adults, identifying patterns of language use in daily interaction, and analyzing the contribution of lifestyle to linguistic variation and evolution. A descriptive quantitative method was employed, using a structured online questionnaire as the primary data collection instrument. Data were collected over a three-week period from 31 participants aged 18–26 from diverse social backgrounds. The findings indicate that participants with more dynamic and modern lifestyles tend to exhibit higher levels of linguistic variation, including frequent use of informal language, code-mixing, and the adjustment of speaking styles according to interlocutors and social situations. The results also indicate variation in language use across domains, particularly in family and social contexts, reflecting the respondents’ sociolinguistic awareness. These findings demonstrate that language change among young adults does not occur randomly but is closely linked to lifestyle, patterns of social interaction, and exposure to digital media. This study contributes to the field of sociolinguistics by providing empirical evidence of the role of lifestyle as a key social factor influencing language change and by emphasizing the importance of everyday social practices in shaping contemporary language use.